A review of Tephritidae and Ulidiidae (Diptera, Tephritoidea) of Croatia - Kovac, D.; Kameneva, E. P.; Korneyev, V. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Started by G. R. von Frauenfeld, R. Schiner and G. Strobl over 120 years ago by collecting several species in “Dalmazien”, studies of the fruit flies (Tephritidae) and picture-winged flies (Ulidiidae) in Croatia to date have been casual and fragmentary. Regular collecting of these families in Modruš (Karlovac County) during 2021–2022 has resulted in a list of 85 species of Tephritidae and 15 species of Ulidiidae presented here, of which 21 Tephritidae and three Ulidiidae species, respectively, are recorded from Croatia for the first time. Examined material and references are listed, and the rare or newly recorded species are illustrated. The status of type specimens of some nominal species described by Frauenfeld and Schiner from Croatia is discussed.